ANALISIS EARNING PER SHARE DAN RETURN ON EQUITY SERTA TINGKAT BUNGA DEPOSITO TERHADAP HARGA SAHAM PERBANKAN DI BURSA EFEK INDONESIA - -, Gunarianto - (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract: The purpose of this research is to know how much the influence of EPS, ROE, Interest Rates on stock prices with the object of the research is by taking the financial report data in 2006 to 2010 on group of finance that listed on Indonesian Stock Exchange and Interest Rates of bank that has been go public. The analysis showed that the EPS, ROE and deposit rates that have been formulated to explain significantly the occurrence of changes in stock prices at the banking company. Of note also that the analysis, the dominant variables affecting the stock price is in the interest rate of deposits with a pattern of relationships in the opposite direction. Thus the results of this study can be used as a basic assumption for potential investors in assessing a company, before making any purchases of shares in the company concerned. Keywords: Earning Per Share (EPS), Return on Equity (ROI), Interest Rate